The Influence of Form- and Meaning-Based Predictions on Cortical Speech Processing Under Challenging Listening Conditions: A MEG Study - Signoret, Carine; Andersen, Lau M.; Dahlström, Örjan; Blomberg, Rina; Lundqvist, Daniel; Rudner, Mary; Rönnberg, Jerker (Frontiers in Neuroscience, 2020)
Under adverse listening conditions, prior linguistic knowledge about the form (i.e. phonology) and meaning (i.e. semantics) help us to predict what an interlocutor is about to say. Previous research has shown that accurate predictions of incoming speech increase speech intelligibility, and that semantic predictions enhance the perceptual clarity of degraded speech even when exact phonological predictions are possible. In addition, working memory (WM) is thought to have specific influence over anticipatory mechanisms by actively maintaining and updating the relevance of predicted versus unpredicted speech inputs. However, a thorough understanding of whether predictions generated at different levels have different kinds of impact on speech processing is lacking in the field. Here, we use MEG to investigate the cortical temporal processing of form and meaning predictions of final words during sentence processing. Our overall aim was to observe how form and meaning deviations from predictions modulate cortical speech processing under adverse listening conditions and investigate the degree to which these deviations are associated with WM capacity. Results indicated that different types of predictions are expressed differently in the auditory N400 and Mismatch Negativity (MMN) components. In particular, MMN was sensitive to the type of deviations (form or meaning) whereas the N400 was sensitive to the strength of deviations rather than the type of deviations. WM capacity was involved in the ability to process phonological incoming information and semantic integration.